Development of scaffolds for tissue engineering applications - Kurniawan, Grace Jasmine (2019)
Alginate has been widely used as cell carriers for cell-based therapy applications due to its intrinsic properties, such as non-toxic and non-antigenicity. However, the bioinert behavior of alginate often resulted in poor cell interaction that resulted in poor survivability of the cells. Thus, an effort to increase the bioactivity was carried out by incorporating Adipose Tissue-derived ECM (Ad-ECM). However, poor distribution of Ad-ECM across the alginate capsules was observed. In addition, the presence of Ad-ECM affected the capsule formation, in terms of its size and shape that are crucial in determining the biological function of the capsules. For instanceStudies have shown there is shape- and size-dependant on capsules fabricated towards fibrosis formation. Thus, the alginate/Ad-ECM precursor solution was was homogenized, in which successfully improved the distribution and the capsule formation. In addition, the capsule formation was highly dependent on the ratio of alginate and Ad-ECM. Results showed that a final concentrations of 1% alginate and 0.5% Ad-ECM provided the right viscosity and the formability of spherical capsules. Under 10 kV and 3-cm parameter, a 1,300.68 ± 37.09 μm capsules in diameter size was successfully fabricated, which could minimize the formation of fibrosis upon implantation. Finally, physicochemical studies were carried out and showed that the presence of Ad-ECM successfully improved the stability and mechanical properties of the alginate. However, the presence of Ad-ECM did not prolong the degradation stability of the capsules. Hence, improvement to slower down the degradation process of Ad-ECM is needed or due to its short term stability, the carrier would be more suitable for drug delivery applications.